The Influence of Shopee Paylater and Harbolnas Ads on Online Customer’s Impulse Buying in Dharmasraya - Dini Elida Putri; Kelik Purwanto; Fenisi Resty; Mayroza Wiska; Eka Ermawati; Anesya Defitri (Greenation Research & Yayasan Global Resarch National, 2023)
Online shopping concept shifted from fulfilling everyday needs to reflecting life style in product purchases. Alternatives of payment method have also encouraged more customers to use online shopping more than before. One of the most recent payment method introduced is Paylater, and Shopee is one of many marketplaces which offers it. Paylater gives online credit payment, without credit card owned by users. To attract more customer’s interest, Shopee launched its twin-date promotion ads (known as Harbolnas or Hari Belanja Nasional ads), offers discounts, vouchers, free delivery, and more. This study aims to analyze partial and simultaneous effect of Shopee Paylater and Harbolnas ads on impulse buying of online customers in Dharmasraya. This research is a quantitative research. A valid and reliable Likert scale questionnaires used to collect data, distributed to 220 samples whom meet the criterias and analyzed using SPSS.20. T-test and F-test used to answer research hyphotesis. The results shows both Shopee paylater and Harbolnas Ads, partially has positive and significant effect on impulse buying, with significance level bellow 0,05. The result also shows that all independent variables simultaneously have positive and significant effect on dependent variable with F test result shows Ftest value more than Ftable value (62,360 > 3,04) and adjusted R Square value is 0,359, which means Shopee paylater and Harbolnas Ads simultaneously influencing 35,9% impulse buying.